Anomalies in terrestrial hydrological cycle – India
bl ’kks/k&i= esa ;g crk;k x;k gS fd lewps fo’o esa fo|eku izkÑfrd lalk/kuksa ds nksguksa ¼VsªLM QqVfizaV½ ds QyLo:Ik fo’o tyok;q Ik)fr vO;ofLFkr gks tkrh gSA tks ks=h; leL;kvksa lesr fo’o tyh; pØ dks vkSj vf/kd rhoz djus ds fy, mRrjnk;h ekuh tk ldrh gSA bl ’kks/k&i= esa ty larqyu fun’kZ ds ek/;e ls Hkkjr esa tyh; ks= ds ekeys esa bl rF; dks le>us dk iz;kl fd;k x;k gSA bl laca/k esa dh xbZ tk¡p ls eq[;r% lewps Hkkjr ds tyh; QyDlksa ij bulks@yulks flXuy ds tyok;q laca/kh nwj laidZ ds izHkkoksa dh tkudkjh izkIr gqbZ gSA It is reported that the traced footprints across the world are the consequences of the perturbed world climate system that might be responsible in intensifying the world hydrological cycle with regional implications. An attempt is made here to understand this fact in case of hydrological regime over India through water balance model. The investigation mainly addresses the climate teleconnection impacts of ENSO/LNSO signal on the hydrological fluxes for All India. , number=4, journal=MAUSAM, author=SARMA , A. A. L. N. and SRINIVAS, S., year=2006, month=Oct., pages=639–652